The Concept of God in Malay Sufi Literature: A Study of the Sufi Poetry of Hamzah Fansuri - Angga Arifka (EL- Hayah, 2025)
This article examines the literary footsteps of Hamzah Fansuri who is known as a famous Sufi and poet in Aceh in the sixteenth and seventeenth centuries. Fansuri’s primary contribution to Malay literature is very significant. As a controversial wujudi Sufi, Fansuri utilized poetry to convey his Sufi experiences and ideas. This article uses a qualitative method to explore and describe his rich mystical views. By using a content analysis approach, this article presents Fansuri’s poetry in order to understand the constellation of his wujudiyah thoughts. This article found that Fansuri succeeded in showing his expertise in conveying his Sufi ideas using the medium of poetry. In addition, he was a key Sufi poet who has introduced the Malay poetic image by creatively adopting Arabic-Persian vocabularies.